The resultant of the given expression 9(3+c+4) using distributive property will be 63 + 9c.
A mixture of variables, numbers, addition, subtraction, multiplication, and division are called expressions.
A statement expressing the equality of two mathematical expressions is known as an equation.
As per the given expression,
9(3+c+4)
⇒ 9(7+c)
By using distribution property,
⇒ 9(7)+9c
⇒63+9c
Hence "The resultant of the given expression 9(3+c+4) using distributive property will be 63 + 9c".
To learn more about expression,
#SPJ2
9(3+c+4)
9(7+c)
9(7)+9c
Answer:
63+9c
B. y = 6x + 1
C. y = -6x + 1
D. y = -6x – 1
The expression into an equivalent form would be; A. y = 6x – 1
Those expressions that might look different but their simplified forms are the same expressions are called equivalentexpressions.
To derive equivalent expressions of some expressions, we can either make it look more complex or simple. Usually, we simplify it.
We need to the expression into an equivalent form.
This expression could also be given as
6x – y = 1
Now, we know that:
6x – y = 1
6x = y + 1
y = 6x - 1
Hence, the required expression into an equivalent form 6x – y = 1 would be; y = 6x - 1
Learn more about expression here;
#SPJ2
Answer:
A. y = 6x – 1
Step-by-step explanation: